Gestures : the do's and taboos of body language around the world - Axtell, Roger E. (New York : Wiley, 1991)
" ... This latest edition includes: updates about the 200 most popular gestures and signals-and dozens of new examples; new sections covering special gestures-from American Sign Language and Tai Chi to flirting and kissing; information to guide you through gestures country by country--from Switzerland to Japan, Nigeria to the Netherlands; amusing anecdotes and helpful hypothetical scenarios."--Publisher description.
The Power of Gestures -- The Most Popular Gestures -- Gestures: Head to Toe -- The ultimate gesture -- The Innocent Abroad's Shortlist -- Country-by-Country Listing.
Includes bibliographical references (page 223) and index.
Keywords: Body language -- Cross-cultural studies; Gesture -- Cross-cultural studies; Etiquette; Cross-cultural studies